2019
DOI: 10.1371/journal.pone.0209532
|View full text |Cite
|
Sign up to set email alerts
|

To examine environmental pollution by economic growth and their impact in an environmental Kuznets curve (EKC) among developed and developing countries

Abstract: This study analyzes the core energy consumption among countries’ specific variables by Environmental Kuznets Curve hypothesis (EKC), for a panel data of 29 (14 developed and 15 developing) countries during the period of 1977–2014. By assessing Generalized Method of Moments (GMM) regressions with first generation tests such as common root, individual Augmented Dickey-Fuller (ADF), and individual root-Fisher-PP which have been computed individually, the results confirm the EKC hypothesis in the case of emissions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 60 publications
5
35
0
Order By: Relevance
“…The more significant aim is to share CO2 emissions and reduce it by different projects. This study is unique because of economic growth, likewise the prior research papers have investigated the dynamic link between developing countries' energy consumption and economic growth (Ito, 2017;Kong & Khan, 2019;Liu. et al, 2018;Tian, Bai, Jia, Liu, & Shi, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The more significant aim is to share CO2 emissions and reduce it by different projects. This study is unique because of economic growth, likewise the prior research papers have investigated the dynamic link between developing countries' energy consumption and economic growth (Ito, 2017;Kong & Khan, 2019;Liu. et al, 2018;Tian, Bai, Jia, Liu, & Shi, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…On the whole, the regional water utilization efficiency in the study area showed a "U-shaped" trend in 2006-2016, which first decreased and then increased and also validated the existence of the "Environmental Kuznets Curve" [31]. Many countries or regions usually choose the road of pollution first and then treatment.…”
Section: Temporal and Spatial Differences In Water Utilization Efficimentioning
confidence: 54%
“…L.noted that it is more easily for Asian students to adapted to different cultural than African students. There is a great potential of social network sites to international students cross-cultural adaptation (Kong & Khan, 2019;Wang, 2015).…”
Section: Cross-cultural Adaptation Of Foreign Students In Chinamentioning
confidence: 99%